Tingkat Pemahaman dan Minat Wisatawan Domestik Terhadap Yoga Sebagai Aktivitas Pelayanan Pariwisata Wellness di Bali - Gustu Rama Bhaskara Putra; Dewa Ayu Putri Sri Masyeni; I Made Indra Wijaya (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[Level of Understanding and Interest of Domestic Tourists in Yoga as a Wellness Tourism Service Activity in Bali] Based on the Global Web Index report (2019), it is said that health tourism travel has experienced growth of 15.3% every year from 2015 to 2017, reaching 830 million trips annually. (8) Indonesia is in the 19th position out of 20 countries as a wellness tourism destination, according to the Global Wellness Tourism Economy 2020 report. (14) Currently, research related to wellness tourism has been intensively carried out, however research specializing in yoga has not been widely studied. This research aims to explore domestic tourists' understanding and interest in yoga as a wellness tourism service activity in Bali. This research is a descriptive study with a cross-sectional design. Implementation in December 2023 – March 2024 with a simple random sampling method. The data analysis used was univariate analysis. The number of samples in this study was 80 people. The research results showed that the characteristics of the respondents were dominated by 47 people (58.8%) who are female, 45 people aged 15 - 25 years (56.3%), 14 people from Jakarta (17.5%), and 37 students (46.3%). A total of 44 respondents really understood the general description of yoga (55.0%), and research respondents were dominated by respondents who often did yoga (more than once a week), as many as 29 people (36.3%). The level of understanding of yoga among research respondents was dominated by 51 respondents (63.8%) who understood yoga. The level of interest in yoga among research respondents was dominated by respondents who had a high level of interest in yoga, with 42 people (52.5%). This research is expected to provide information regarding domestic tourists' understanding and interest in yoga as a wellness tourism service activity in Bali.